2018
DOI: 10.1186/s12889-018-5446-1
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of workplace social distancing measures in reducing influenza transmission: a systematic review

Abstract: BackgroundSocial distancing is one of the community mitigation measures that may be recommended during influenza pandemics. Social distancing can reduce virus transmission by increasing physical distance or reducing frequency of congregation in socially dense community settings, such as schools or workplaces. We conducted a systematic review to assess the evidence that social distancing in non-healthcare workplaces reduces or slows influenza transmission.MethodsElectronic searches were conducted using MEDLINE,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
329
0
15

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 374 publications
(351 citation statements)
references
References 46 publications
7
329
0
15
Order By: Relevance
“…25 This observation is consistent with the conclusions of a review of 15 studies that found a median reduction of 23% (range 12-82) in the cumulative influenza A H1N1 attack rate with workplace distancing alone. 26 The implementation of such a control measure, however, is likely to have an acute societal economic effect on individuals who must work from home or take leave, especially if reimbursement is not possible. Thus, decision making becomes a function of risk as to whether the imported cases have or will infect the local population and cause a local outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…25 This observation is consistent with the conclusions of a review of 15 studies that found a median reduction of 23% (range 12-82) in the cumulative influenza A H1N1 attack rate with workplace distancing alone. 26 The implementation of such a control measure, however, is likely to have an acute societal economic effect on individuals who must work from home or take leave, especially if reimbursement is not possible. Thus, decision making becomes a function of risk as to whether the imported cases have or will infect the local population and cause a local outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…Not only this, but if a large proportion of the population continues to work while unwell, low compliance will render the various forms of social distancing less effective, as low-income workers are forced to choose between financial and physical health. Indeed, this behaviour has already been observed in the workplace in previous pandemics: workers without access to paid sick leave were more likely to work while unwell than those with paid sick leave (14). A study in China after the H7N9 epidemic found that only 7% of people reported willingness to self-quarantine (15).…”
Section: Discussionmentioning
confidence: 85%
“…These measures greatly changed age-specific mixing patterns within the population in previous outbreak response efforts for other respiratory infectious diseases. 5,6 Although travel restrictions undoubtedly had a role in reducing exportations of infections outside Wuhan and delayed the onset of outbreaks in other regions, 7,8 changes in mixing patterns affected the trajectory of the outbreak within Wuhan itself. To estimate the effects of physical distancing measures on the progression of the COVID-19 epidemic, we look at Wuhan, hoping to provide some insights for the rest of the world.…”
Section: Introductionmentioning
confidence: 99%